Strategi Jemput Bola dalam Meningkatkan Kenyamanan Pelanggan pada Fresh Clean di Kecamatan Bengkayang (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study aims to describe the implementation of the outreach strategy through the perspective of service convenience theory at Fresh Clean services in Bengkayang District. The study used a descriptive qualitative approach with data collection techniques through observation, in-depth interviews, and documentation. The research informants consisted of ten customers who had used the pick-up and delivery service at least four times. Data were analyzed using the Miles and Huberman interactive model which includes data reduction, data presentation, and conclusion drawing. The results of the study indicate that the implementation of the outreach strategy provides convenience in terms of accessibility, time efficiency, and ease of service for customers. Customers assess the pick-up and delivery service is able to reduce physical burden and time because they do not need to come directly to the business location. This strategy also increases customer satisfaction through friendly communication, responsive service, and satisfactory laundry quality. However, the study found several obstacles, such as inconsistency in delivery times, delays in communication responses, and operational limitations due to the business being managed independently. Overall, the outreach strategy proved effective in increasing customer convenience, interest, and repeat purchase tendencies, while also becoming a competitive advantage for Fresh Clean amidst competition in the service business